Enzymatically modified isoquercitrin supplementation intensifies plantaris muscle fiber hypertrophy in functionally overloaded mice. Issue 1 (2nd September 2017) - Kohara, Akiko; Machida, Masanao; Setoguchi, Yuko; Ito, Ryouichi; Sugitani, Masanori; Maruki-Uchida, Hiroko; Inagaki, Hiroyuki; Ito, Tatsuhiko; Omi, Naomi; Takemasa, Tohru
Abstract: Background: Enzymatically modified isoquercitrin (EMIQ) is produced from rutin using enzymatic hydrolysis followed by treatment with glycosyltransferase in the presence of dextrin to add glucose residues. EMIQ is absorbed in the same way as quercetin, a powerful antioxidant reported to prevent disused muscle atrophy by targeting mitochondria and to have ergogenic effects. The present study investigated the effect of EMIQ on skeletal muscle hypertrophy induced by functional overload. Methods: In Study 1, 6-week-old ICR male mice were divided into 4 groups: sham-operated control, sham-operated EMIQ, overload-operated control, and overload-operated EMIQ groups. In Study 2, mice were divided into 3 groups: overload-operated whey control, overload-operated whey/EMIQ (low dose), and overload-operated whey/EMIQ (high dose) groups. The functional overload of the plantaris muscle was induced by ablation of the synergist (gastrocnemius and soleus) muscles. EMIQ and whey protein were administered with food. Three weeks after the operation, the cross-sectional area and minimal fiber diameter of the plantaris muscle fibers were measured. Results: In Study 1, functional overload increased the cross-sectional area and minimal fiber diameter of the plantaris muscle. EMIQ supplementation significantly increased the cross-sectional area and minimal fiber diameter of the plantaris muscle in both the sham-operated and overload-operated groups. In Study 2, EMIQ supplementation combined with whey protein administration significantly increased the cross-sectional area and minimal fiber diameter of the plantaris muscle. Conclusion: EMIQ, even when administered as an addition to whey protein supplementation, significantly intensified the fiber hypertrophy of the plantaris muscle in functionally overloaded mice. EMIQ supplementation also induced fiber hypertrophy of the plantaris in sham-operated mice.